Small Cell Carcinoma of the Gallbladder: (18)F-FDG PET/CT Imaging Features—A Case Report - Kim, Da-Mi (Springer-Verlag, 2010)
The diagnostic role of (18)F-fluorodeoxyglucose ((18)F-FDG) positron emission tomography (PET)/computed tomography (CT) for gallbladder small cell carcinoma has not been reported. A knowledge of the imaging characteristic features of this malignancy can be useful. Here we report a rare case of a patient who had various diagnostic imaging modalities, including (18)F-FDG PET/CT.